SOMATOTYPES IN THE ADOLESCENT PERIOD – A REVIEW ARTICLE - Bojadzieva, Biljana Stojanoska; Matveeva, Niki; Zafirova, Biljana; Trpkovska, Biljana; Cadikovska, Elizabeta; Angelovska, Irina; Pejkovska, Sava; Kordoska, Jovana (Journal of Morphological Sciences, 2025)
Growth and development in children and adolescents are dynamic, interrelated processes that reflect both genetic and environmental influences. Anthropometric assessment and somatotype classification are essential tools for evaluating these processes, offering insights into body composition, health risks, and physical performance. Somatotype, defined by three components: endomorphy (fat), mesomorphy (muscle), and ectomorphy (linearity) provides a standardized method to describe physique and its variations across age and sex. This paper reviews growth patterns, the historical development of somatotyping methods, and their application in children and adolescents. Evidence shows that somatotype characteristics vary significantly during puberty: endomorphy tends to increase in females, while mesomorphy predominates in males, particularly in late adolescence. Ectomorphy peaks during periods of rapid height growth, then declines with advancing age. These shifts are influenced by hormonal changes, nutrition, physical activity, and socio-economic factors. Understanding somatotype development has clinical and applied relevance. It assists in monitoring population health, identifying risks of obesity and related metabolic conditions, and guiding individualized approaches in sports and physical education. While somatotype is strongly determined by genetic factors, lifestyle interventions especially balanced nutrition and regular physical activity can improve body composition and overall health outcomes.   Keywords: growth, adolescence, somatotype, anthropometry, body composition, puberty.